Idiopathic Orbital Inflammation Associated With Necrotizing Scleritis and Temporal Bone Inflammation. Issue 4 (July 2016) - Kasi, Sundeep K.; Kim, H. Jane; Basham, Ryan P.; Cunningham, Emmett T.; Sy, Aileen; Lustig, Larry; Kersten, Robert C.
Abstract : The authors present a case of aggressive idiopathic orbital inflammation producing necrotizing scleritis along with synchronous tumefactive fibroinflammatory lesion of the temporal bone. A young woman with no medical history presented with sectoral scleritis and mildly reduced vision. Response to initial treatment, which included topical and systemic corticosteroids, as well as systemic nonsteroidal anti-inflammatory drugs, was limited. Over the following months, signs of orbital inflammation developed, including ptosis, proptosis, and limited extraocular motility. MRI revealed both orbital and ipsilateral temporal bone masses. An orbital biopsy was performed revealing a mixed inflammatory infiltrate, whereas a biopsy of the temporal bone mass revealed a tumefactive fibroinflammatory lesion. Biopsy showed no histopathologic evidence of infection nor neoplasm. The patient eventually responded to treatment with systemic prednisone, azathioprine, and rituximab. Abstract : We present a young woman with aggressive idiopathic orbital inflammation producing necrotizing scleritis along with synchronous tumefactive fibro-inflammatory lesion of the temporal bone eventually controlled with rituximab.